Experimental measurements of flow mixing in cold leg of a pressurized water reactor. (1st June 2020) - Orea, Daniel; Vaghetto, Rodolfo; Nguyen, Thien; Hassan, Yassin
Highlights: Concurrent velocity and concentration fields of buoyancy-driven flow mixing in cold leg have been presented. Methods to quantify uncertainty of the measurements have been discussed. The experimental data produced will support the validation of Computational Fluid Dynamics tools and methods. Abstract: The main objective of OECD/NEA Cold Leg Mixing CFD-UQ Benchmark exercise is to evaluate the use of CFD simulations for safety issues related to mixing phenomena in the cold leg and downcomer of a Pressurized Water Reactor. An experimental facility has been designed and constructed to collect measurements of density-driven the flow mixing. Special techniques have been applied to simulate high density difference fluids while maintaining optical properties required to apply laser-based flow measurements techniques. Particle Image Velocimetry (PIV) was applied to determine the velocity field, combined with Laser Induced Fluorescence (LIF) to simultaneously capture the concentration of species. Pressure drop, cold front speed, and physical properties of the solutions have been presented. Results and measurement uncertainty are discussed. This article provides a unique set of data to support the advancement and the assessment of CFD codes in predicting mixing in buoyancy-driven flows in nuclear and non-nuclear applications.